Studying the suitability of Al-Thawra Dam Lake water for drinking purposes using quality indicators ( NSF- CCME) - حميشة مادلين; عادل عوض; رائد جعفر (Latakia University Journal -Engineering Sciences Series, 2024)
The study aimed to determine the suitability of the water of Al-Thawra Dam Lake in Latakia Governorate for drinking purposes using quality indicators ( NSF-CCME) Physical, chemical and microbial analyzes of the lake’s water were conducted during a complete hydrological cycle during the period from March (2022) to April (2023), Samples were taken from four locations: 1- Lake entrance ( S1) -2- Spillway ( S2) 3- Irrigation socket ( S3) 4- Beheira( S4) The study concluded: When applying the World Water Quality Index (NSF WQI), the lake’s water quality fell under Class (C) and was therefore classified as Average quality at all monitoring points. While the lake’s water quality according to the Canadian Ministers of the Environment Index (CCME WQI) at all monitoring sites falls under the marginal classification, and thus the water quality is frequently threatened or poor and often deviates from normal levels Therefore, we find that the lake’s water, according to the two indicators (NSF-CCME), is not suitable for drinking and needs treatment.